Incidence and variables associated with 30‐day mortality after lung transplantation. Issue 2 (20th January 2019) - Banga, Amit; Mohanka, Manish; Mullins, Jessica; Bollineni, Srinivas; Kaza, Vaidehi; Huffman, Lynn; Peltz, Matthias; Bajona, Pietro; Wait, Michael; Torres, Fernando
Abstract: Background: With the introduction of the lung allocation score (LAS), sicker patients are prioritized for lung transplantation (LT). There is a lack of data regarding variables independently associated with 30‐day mortality after LT. Methods: We queried the UNOS database for adult patients undergoing LT between 1989 and 2014. Patients with dual organ or previous transplantation and those with missing survival data were excluded. Mortality during the first 30 days after LT was the primary outcome variable. Results: The yearly trends indicate a statistically significant reduction in the 30‐day mortality during the study period ( P  < 0.001, overall mortality: 5.5%) which has continued in the post‐LAS era ( P  = 0. 014, overall mortality: 3.6%). Among patients with 30‐day mortality, "primary non‐function" (n = 118, 72.8%) was reported as the most common etiology. Transplant indication of vascular diseases, history of non‐transplant cardiac or lung surgery, mean pulmonary pressures >35 mm Hg, disabled functional status, ECMO support, high LAS, ischemic time >6 hours, and blunt injury as the mechanism of donor death are independently associated with 30‐day mortality. Conclusion: The incidence of early mortality after LT continues to decline in the post‐LAS era. Apart from the mechanism of donor death and ischemic time, early mortality appears to be primarily driven by the recipient characteristics.